Highly stain-resistant artificial marble, preparation method thereof and surface treatment agent thereof

By using fiber-modified unsaturated polyester resin and surface-treated composite fibers, the problem of poor stain resistance of artificial marble in the prior art is solved, and higher stain resistance and service life are achieved.

CN119330637BActive Publication Date: 2025-04-11WARNER FLUORINE MATERIALS (GUANGZHOU) CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411459640.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-04-11
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

The existing artificial marble has poor stain resistance, especially in kitchen scenarios, which are easily penetrated by non-colored substances such as soy sauce and chili oil, resulting in increased cleaning difficulty and shortened service life.

Method used

High stain-resistant artificial marble consisting of fiber-modified unsaturated polyester resin, fillers, accelerators, dispersants and initiators is used, and surface-treated composite fibers and carbon nanotubes are used to enhance the bonding capacity and density of the material.

Benefits of technology

It significantly reduces the porosity of artificial marble, improves its structural density and anti-fouling ability, extends its service life, and improves the user experience.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330637B_ABST
    Figure CN119330637B_ABST
Patent Text Reader

Abstract

The present application provides a highly stain-resistant artificial marble, a preparation method thereof and a surface treatment agent thereof, wherein the highly stain-resistant artificial marble is composed of a fiber-modified unsaturated polyester resin, a filler, a promoter, a dispersant, and an initiator, and the unsaturated polyester resin is modified by a composite fiber composed of carbon fiber, glass fiber, PVA fiber, and PE fiber. When the unsaturated polyester resin undergoes a chain extension reaction, a chemical bond can be formed between the composite fiber interface and the unsaturated polyester chain segment, thereby significantly improving the binding ability of the two. Furthermore, the introduction and surface treatment of the composite fiber can provide a binding site for the filler, refine the microstructure of the artificial marble, and improve its density. After the composite fiber extends to the interface, it can increase the binding site for the surface modifier, significantly improve its adhesion ability, and thus improve the anti-fouling ability of the surface of the artificial marble. The artificial marble has the advantages of significantly improved anti-fouling ability, long service life, good use experience, and easy promotion and implementation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of decoration building materials, and specifically relates to a highly stain-resistant artificial marble, a preparation method thereof, and a surface treatment agent thereof. Background Art

[0002] In the prior art, artificial marble is a decorative material that imitates the appearance of natural marble. It is made of crushed natural marble or granite as filler, combined with cement, gypsum and unsaturated polyester resin and other adhesives, through stirring, molding, grinding and polishing. With the improvement of people's material living standards, artificial marble has been widely used in various fields in recent years, such as kitchen stoves, background walls, floor decoration, etc. However, due to the poor water resistance, acid and alkali resistance, oil resistance and other anti-penetration effects of the early products, the beauty of the later use effect is seriously affected;

[0003] In the prior art, marble surface treatment agents can be used to improve the gloss, hardness, anti-slip and anti-fouling ability of marble. When used with artificial marble, the service life and surface anti-fouling ability of artificial marble can be improved. However, in the prior art, the bonding ability between the resin and the filler in the artificial marble is poor, the porosity of the artificial marble is high after molding, and the bonding ability between the marble surface treatment agent and the surface of the artificial marble is poor. After long-term use, especially in kitchen use scenarios, the surface treatment agent will peel off from the marble surface, thereby accelerating the aging of the marble surface, allowing colored pollutants such as soy sauce and spicy soy sauce to penetrate into the interior of the artificial marble, significantly increasing its cleaning difficulty and reducing the user experience. Therefore, improvements are urgently needed. Summary of the invention

[0004] The present application aims to solve the technical problems that in the prior art, artificial marble is usually composed of resin and filler, has a high porosity, and has poor stain resistance during actual use. In the kitchen scene, colored substances such as soy sauce and chili oil will penetrate into the artificial marble, significantly increasing the difficulty of cleaning the kitchen. In addition, the existing marble surface treatment agent has poor bonding ability with the surface of artificial marble. In the kitchen scene, the surface treatment agent is easy to peel off. After peeling, the pollutants will quickly penetrate into the artificial marble, significantly increasing the difficulty of cleaning the kitchen. A highly stain-resistant artificial marble is proposed;

[0005] In order to solve the technical problem proposed by the present application, the present application also proposes a method for preparing highly stain-resistant artificial marble;

[0006] In order to solve the technical problem raised by the present application, the present application also provides an artificial marble surface treatment agent, which is coated on the outer surface of the artificial marble.

[0007] The present application adopts the following scheme, a highly stain-resistant artificial marble, which is composed of the following components by weight: 22-35 parts of fiber-modified unsaturated polyester resin, 43-55 parts of filler, 1-5 parts of accelerator, 1-5 parts of dispersant and 3-8 parts of initiator;

[0008] The fiber-modified unsaturated polyester resin is an unsaturated polyester resin obtained by modifying composite fibers;

[0009] The composite fiber is a composite of any two or more of carbon fiber, glass fiber, PVA fiber and PE fiber.

[0010] In one embodiment, the composite fiber is composed of the following components by weight: 5-8 parts of carbon fiber, 10-23 parts of glass fiber and 1-5 parts of PE fiber;

[0011] The diameter of the carbon fiber is 8-12 μm, the length of the carbon fiber is 1.5-5.5 mm, and the tensile strength of the carbon fiber is 1950-2560 MPa;

[0012] The diameter of the glass fiber is 24-50 μm, the length of the glass fiber is 0.7-1.2 mm, and the tensile strength of the glass fiber is 1140-1330 MPa;

[0013] The diameter of the PE fiber is 15-21 μm, the length of the carbon fiber is 1.2-4.5 mm, and the tensile strength of the carbon fiber is 1950-2560 MPa.

[0014] By selecting carbon fiber, glass fiber and PE fiber as the main components of composite fiber, the disadvantage of low strength of glass fiber is compensated, and the structural strength of artificial marble can be effectively improved.

[0015] In one embodiment, the composite fiber is prepared after surface modification, and the surface modification of the composite fiber comprises the following steps:

[0016] Step 101. Put the composite fiber, tetraethyl orthosilicate and ethanol into a reaction kettle in sequence, and add the composite surface modifier drop by drop at room temperature and 200 rpm, and after the addition is completed, the activated composite fiber is obtained;

[0017] Step 102. Add ammonia water dropwise to the activated composite fiber prepared in step 101, perform ultrasonic treatment at room temperature and 2000 Hz for 30 min, and then perform constant temperature reaction at 50° C. in a water bath for 18 h to obtain a crude composite fiber;

[0018] Step 103. The crude composite fiber prepared in step 102 is transferred to room temperature and allowed to stand for 36 hours, and then washed, filtered and dried in sequence to obtain the composite fiber after surface modification.

[0019] The unsaturated polyester resin is modified by using surface-treated composite fibers, and SiO2 grains with a particle size of nanometers are branched on the surface of the composite fibers, which significantly increases the specific surface area of ​​the composite fibers. During the blending process with the unsaturated polyester resin, the binding sites are significantly increased. During the chain extension process, C-Si-H bonds can be formed between the composite fibers and the resin, which significantly increases the binding ability. An interpenetrating network can be formed inside the resin. After blending with the filler, due to the composite fibers in the resin and the carbon nanotubes in the filler, when the large-particle filler is embedded in the resin, the SiO2 grains on the composite fibers can absorb the carbon nanotubes and the small-particle filler to fill the gaps. The carbon nanotubes can fit tightly with the gaps through the C-Si-H bonds, refine the internal structure of the artificial marble, and then significantly reduce the porosity of the artificial marble, making the artificial marble structure denser.

[0020] In one embodiment, the method for preparing the fiber-modified unsaturated polyester comprises the following steps:

[0021] Step 201. Put the composite fiber, unsaturated polyester resin base material, dispersant and ethyl acetate into a high-speed dispersing kettle in sequence, and disperse them at 50° C. and 2000 rpm for 30 minutes to obtain a crude fiber-modified resin;

[0022] Step 202. Ethyl acetate and deionized water are added to the crude fiber-modified resin prepared in step 201 in sequence, and dispersed for 15 minutes in a water bath at 45° C., nitrogen atmosphere, and 2600 rpm to obtain an emulsion;

[0023] Step 203. The emulsion prepared in step 202 is transferred to a spray dryer, and after atomization drying at a dryer inlet temperature of 155°C and a dryer outlet temperature of 95°C, it is allowed to stand and cool at 10-16°C to obtain a fiber-modified unsaturated polyester.

[0024] In one embodiment, the filler is any one of calcium carbonate, α-alumina, carbon nanotubes and hollow microspheres, or a combination of more than one of them.

[0025] In one embodiment, the filler is composed of the following components, by weight: 10-15 parts of calcium carbonate A, 5-8 parts of calcium carbonate B, 5-8 parts of α-alumina, 1-5 parts of carbon nanotubes and 1-3 parts of hollow microspheres;

[0026] The particle size of the calcium carbonate A is 250-330 μm, the particle size of the calcium carbonate B is 50-120 μm, the particle size of the α-alumina is 87-180 μm, and the length of the carbon nanotube is 10-50 mm.

[0027] In one of the embodiments, the filler is obtained after surface treatment, and the filler surface treatment method comprises the following steps: calcium carbonate A, calcium carbonate B, α-alumina, carbon nanotubes and hollow microspheres are put into a stirring tank in sequence, and then a silane coupling agent is added dropwise into the stirring tank, and after stirring at 100 rpm for 20 minutes, soaking for 2 hours, washing, filtering and drying in sequence to obtain the filler.

[0028] In order to solve the technical problem raised by the present application, the present application also provides a method for preparing highly stain-resistant artificial marble, comprising the following steps:

[0029] Step 301. Put the fiber-modified unsaturated polyester resin, filler, accelerator, dispersant and initiator into a stirring kettle in sequence, and disperse them uniformly in a water bath at 65° C., 2200 rpm, nitrogen atmosphere, and -0.05 MPa to obtain an artificial marble slurry;

[0030] Step 302. After applying a proper amount of release agent on the inner surface of the molding mold, the artificial marble slurry prepared in step 301 is transferred to the mold, solidified under the conditions of 150°C and 0.5Mpa, and cooled and demolded to obtain highly stain-resistant artificial marble.

[0031] In order to solve the technical problem proposed by the present application, the present application also provides an artificial marble surface treatment agent, which is applied to the outer surface of the above-mentioned highly stain-resistant artificial marble;

[0032] The artificial marble surface treatment agent is composed of the following components by weight: 7-13 parts of silicate, 8-10 parts of neutral silica sol, 2-4 parts of propyltrimethoxysilane, 12-16 parts of methyl silicate, 0.2-0.5 parts of auxiliary agent and appropriate amount of deionized water;

[0033] The preparation method of the artificial marble surface treatment agent comprises the following steps:

[0034] Deionized water silicate, neutral silica sol, propyltrimethoxysilane, methyl silicate and additives are sequentially put into a stirring kettle, dispersed for 10-15 minutes at room temperature and 1200 rpm, and then the pH value is adjusted to 8.0 to obtain an artificial marble surface treatment agent.

[0035] In one embodiment, the silicate is composed of the following components by weight: 3-5 parts of lithium silicate with an average particle size of 4.8 mm, 3-5 parts of lithium silicate with an average particle size of 4 mm, and 1-3 parts of sodium silicate with an average particle size of 3.5 mm;

[0036] The methyl silicate is composed of the following components by weight: 6-8 parts of potassium methyl silicate and 6-8 parts of sodium methyl silicate.

[0037] Compared with the prior art, this application has the following beneficial effects:

[0038] The present application provides a highly stain-resistant artificial marble, a preparation method thereof and a surface treatment agent thereof, wherein the highly stain-resistant artificial marble is composed of a fiber-modified unsaturated polyester resin, a filler, a promoter, a dispersant, and an initiator, and the unsaturated polyester resin is modified by a composite fiber composed of carbon fiber, glass fiber, PVA fiber, and PE fiber. When the unsaturated polyester resin undergoes a chain extension reaction, a chemical bond can be formed between the composite fiber interface and the unsaturated polyester chain segment, thereby significantly improving the binding ability of the two. Furthermore, the introduction and surface treatment of the composite fiber can provide a binding site for the filler, refine the microstructure of the artificial marble, reduce the number of artificial pores in the artificial marble, reduce the porosity of the artificial marble, and improve its density. After the composite fiber extends to the interface, it can increase the binding site for the surface modifier, significantly improve its adhesion ability, and thereby improve the anti-fouling ability of the surface of the artificial marble. The artificial marble has the advantages of significantly improved anti-fouling ability, long service life, good use experience, and easy promotion and implementation. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 It is a schematic diagram of the microstructure of the fiber-modified unsaturated polyester resin of the present application.

[0040] Figure 2 It is a schematic diagram of the microstructure of the modified composite fiber in the fiber-modified unsaturated polyester resin of the present application. Specific embodiments

[0041] The specific parameters of each fiber in the composite fiber in Table 1 are as follows:

[0042] The average diameter of the carbon fiber is 9.3 μm, the average length of the carbon fiber is 1.6 mm, and the average tensile strength of the carbon fiber is 1955 MPa;

[0043] The average diameter of the glass fiber is 33 μm, the average length of the glass fiber is 0.91 mm, and the average tensile strength of the glass fiber is 1187 MPa;

[0044] The average diameter of the PE fiber is 18.2 μm, the average length of the carbon fiber is 3.5 mm, and the average tensile strength of the carbon fiber is 2201 MPa.

[0045] Table 1 Composite fiber components

[0046] Components (parts) Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Carbon Fiber 5.1 serving 7.3 servings 7.9 servings - - 7.9 servings - Fiberglass 11.6 servings 15.9 copies 21.8 copies - 21.8 copies 21.8 copies - PE fiber 1.6 servings 3.2 servings 4.8 servings - - 4.8 servings -

[0047] The specific parameters of each component in the filler in Table 2 are as follows:

[0048] The average particle size of the calcium carbonate A is 268 μm, the particle size of the calcium carbonate B is 65 μm, the particle size of the α-alumina is 123 μm, and the length of the carbon nanotube is 18 mm.

[0049] Table 2 Filling composition

[0050] Components (parts) Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Calcium carbonate A 11.2 servings 13.3 servings 14.7 servings 14.7 servings 14.7 servings 18.8 servings 18.8 servings Calcium carbonate B 6.1 servings 7.2 servings 7.9 servings 7.9 servings 7.9 servings 7.9 servings 7.9 servings Alpha Alumina 6.4 servings 7.1 servings 7.8 servings 7.8 servings 7.8 servings 7.8 servings 7.8 servings Carbon Nanotubes 2.1 serving 3.3 servings 4.1 servings 4.1 servings 4.1 servings - -

[0051] The specific parameters of each component in Table 4 are as follows:

[0052] The silicate is composed of the following components by weight: 3 parts of lithium silicate with an average particle size of 4.8 mm, 5 parts of lithium silicate with an average particle size of 4 mm, and 1 part of sodium silicate with an average particle size of 3.5 mm;

[0053] The methyl silicate is composed of the following components by weight: 7 parts of potassium methyl silicate and 8 parts of sodium methyl silicate.

[0054] Table 4 Components of marble surface treatment agent

[0055] Components (parts) Example 1 Example 2 Example 3 Silicate 7.5 servings 11.3 servings 12.7 servings Neutral silica sol 8.1 servings 9.3 servings 9.8 servings Propyltrimethoxysilane 2.1 serving 3.5 servings 3.8 servings Methyl silicate 12.6 servings 14.5 servings 15.7 servings Additives 0.2 parts 0.3 parts 0.5 serving

[0056] Example 1

[0057] (1) The method for preparing the composite fiber comprises the following steps:

[0058] Step 101. According to the composite fiber component table shown in Table 1, composite fiber, tetraethyl orthosilicate and ethanol are sequentially put into a reaction kettle, and a composite surface modifier is dripped dropwise at room temperature and 200 rpm, and activated composite fiber is obtained after the dripping is completed;

[0059] The composite surface modifier is obtained by mixing CTAB and a silane coupling agent in a mass ratio of 1:1;

[0060] The mass ratio of composite fiber, tetraethyl orthosilicate, ethanol and composite surface modifier is 1:5:15:2;

[0061] Step 102. Add ammonia water dropwise to the activated composite fiber prepared in step 101, perform ultrasonic treatment at room temperature and 2000 Hz for 30 min, and then perform constant temperature reaction at 50° C. in a water bath for 18 h to obtain a crude composite fiber;

[0062] Among them, the mass ratio of activated composite fiber to ammonia water is 10:2;

[0063] Step 103. The crude composite fiber prepared in step 102 is transferred to room temperature and allowed to stand for 36 hours, and then washed, filtered and dried in sequence to obtain the composite fiber after surface modification.

[0064] (2) The method for preparing the fiber-modified unsaturated polyester resin comprises the following steps:

[0065] Step 201. Put the composite fiber, unsaturated polyester resin base material, dispersant and ethyl acetate into a high-speed dispersing kettle in sequence, and disperse them at 50° C. and 2000 rpm for 30 minutes to obtain a crude fiber-modified resin;

[0066] The mass ratio of composite fiber, unsaturated polyester resin base material, dispersant and ethyl acetate is 2:4:1:10;

[0067] Step 202. Ethyl acetate and deionized water are added to the crude fiber-modified resin prepared in step 201 in sequence, and dispersed for 15 minutes in a water bath at 45° C., nitrogen atmosphere, and 2600 rpm to obtain an emulsion;

[0068] Among them, the mass ratio of crude fiber modified resin, ethyl acetate and deionized water is 2:3:10;

[0069] Step 203. The emulsion prepared in step 202 is transferred to a spray dryer, and after atomization drying at a dryer inlet temperature of 155°C and a dryer outlet temperature of 95°C, it is allowed to stand and cool at 10°C to obtain a fiber-modified unsaturated polyester.

[0070] (3) The preparation method of the filler comprises the following steps:

[0071] According to the filler component table shown in Table 2, calcium carbonate A, calcium carbonate B, α-alumina, carbon nanotubes and hollow microspheres were put into a stirring tank in sequence, and then a silane coupling agent was added dropwise into the stirring tank. After stirring for 20 minutes at 100 rpm and soaking for 2 hours, the filler was obtained by washing, filtering and drying in sequence.

[0072] (4) A method for preparing highly stain-resistant artificial marble comprises the following steps:

[0073] Step 301. According to the component table shown in Table 3, fiber-modified unsaturated polyester resin, filler, accelerator, dispersant and initiator are sequentially added into a stirring kettle, and dispersed evenly in a water bath at 65° C., 2200 rpm, nitrogen atmosphere, and -0.05 MPa to obtain artificial marble slurry;

[0074] Step 302. After applying a proper amount of release agent on the inner surface of the molding mold, the artificial marble slurry prepared in step 301 is transferred to the mold, solidified under the conditions of 150°C and 0.5Mpa, and cooled and demolded to obtain highly stain-resistant artificial marble.

[0075] (5) An artificial marble surface treatment agent comprises the following steps:

[0076] According to the component list shown in Table 4, deionized water silicate, neutral silica sol, propyltrimethoxysilane, methyl silicate and additives were sequentially put into a stirring tank, dispersed for 10 minutes at room temperature and 1200 rpm, and the pH value was adjusted to 8.0 to obtain an artificial marble surface treatment agent.

[0077] (6) A method for preparing artificial marble for kitchen use comprises the following steps:

[0078] The artificial marble surface treatment agent prepared above was sprayed on the outer surface of the artificial marble prepared above using a spray gun, and after drying at room temperature, kitchen artificial marble was obtained. The average thickness of the coating on the outer surface of the artificial marble was 0.8 mm.

[0079] Example 2

[0080] (1) The method for preparing the composite fiber comprises the following steps:

[0081] Step 101. According to the composite fiber component table shown in Table 1, composite fiber, tetraethyl orthosilicate and ethanol are sequentially put into a reaction kettle, and a composite surface modifier is dripped dropwise at room temperature and 200 rpm, and activated composite fiber is obtained after the dripping is completed;

[0082] The composite surface modifier is obtained by mixing CTAB and a silane coupling agent in a mass ratio of 1:1;

[0083] The mass ratio of composite fiber, tetraethyl orthosilicate, ethanol and composite surface modifier is 1:5:15:2;

[0084] Step 102. Add ammonia water dropwise to the activated composite fiber prepared in step 101, perform ultrasonic treatment at room temperature and 2000 Hz for 30 min, and then perform constant temperature reaction at 50° C. in a water bath for 18 h to obtain a crude composite fiber;

[0085] Among them, the mass ratio of activated composite fiber to ammonia water is 10:3;

[0086] Step 103. The crude composite fiber prepared in step 102 is transferred to room temperature and allowed to stand for 36 hours, and then washed, filtered and dried in sequence to obtain the composite fiber after surface modification.

[0087] (2) The method for preparing the fiber-modified unsaturated polyester resin comprises the following steps:

[0088] Step 201. Put the composite fiber, unsaturated polyester resin base material, dispersant and ethyl acetate into a high-speed dispersing kettle in sequence, and disperse them at 50° C. and 2000 rpm for 30 minutes to obtain a crude fiber-modified resin;

[0089] The mass ratio of composite fiber, unsaturated polyester resin base material, dispersant and ethyl acetate is 2:6:1:10;

[0090] Step 202. Ethyl acetate and deionized water are added to the crude fiber-modified resin prepared in step 201 in sequence, and dispersed for 15 minutes in a water bath at 45° C., nitrogen atmosphere, and 2600 rpm to obtain an emulsion;

[0091] Among them, the mass ratio of crude fiber modified resin, ethyl acetate and deionized water is 2:3:10;

[0092] Step 203. The emulsion prepared in step 202 is transferred to a spray dryer, and after atomization drying at a dryer inlet temperature of 155°C and a dryer outlet temperature of 95°C, it is allowed to stand and cool at 12°C to obtain a fiber-modified unsaturated polyester.

[0093] (3) The preparation method of the filler comprises the following steps:

[0094] According to the filler component table shown in Table 2, calcium carbonate A, calcium carbonate B, α-alumina, carbon nanotubes and hollow microspheres were put into a stirring tank in sequence, and then a silane coupling agent was added dropwise into the stirring tank. After stirring for 20 minutes at 100 rpm and soaking for 2 hours, the filler was obtained by washing, filtering and drying in sequence.

[0095] (4) A method for preparing highly stain-resistant artificial marble comprises the following steps:

[0096] Step 301. According to the component table shown in Table 3, fiber-modified unsaturated polyester resin, filler, accelerator, dispersant and initiator are sequentially added into a stirring kettle, and dispersed evenly in a water bath at 65° C., 2200 rpm, nitrogen atmosphere, and -0.05 MPa to obtain artificial marble slurry;

[0097] Step 302. After applying a proper amount of release agent on the inner surface of the molding mold, the artificial marble slurry prepared in step 301 is transferred to the mold, solidified under the conditions of 150°C and 0.5Mpa, and cooled and demolded to obtain highly stain-resistant artificial marble.

[0098] (5) An artificial marble surface treatment agent comprises the following steps:

[0099] According to the component list shown in Table 4, deionized water silicate, neutral silica sol, propyltrimethoxysilane, methyl silicate and additives were sequentially put into a stirring tank, dispersed for 12 minutes at room temperature and 1200 rpm, and the pH value was adjusted to 8.0 to obtain an artificial marble surface treatment agent.

[0100] (6) A method for preparing artificial marble for kitchen use comprises the following steps:

[0101] The artificial marble surface treatment agent prepared above was sprayed on the outer surface of the artificial marble prepared above using a spray gun, and after drying at room temperature, kitchen artificial marble was obtained. The average thickness of the coating on the outer surface of the artificial marble was 0.8 mm.

[0102] Example 3

[0103] (1) The method for preparing the composite fiber comprises the following steps:

[0104] Step 101. According to the composite fiber component table shown in Table 1, composite fiber, tetraethyl orthosilicate and ethanol are sequentially put into a reaction kettle, and a composite surface modifier is dripped dropwise at room temperature and 200 rpm, and activated composite fiber is obtained after the dripping is completed;

[0105] The composite surface modifier is obtained by mixing CTAB and a silane coupling agent in a mass ratio of 1:1;

[0106] The mass ratio of composite fiber, tetraethyl orthosilicate, ethanol and composite surface modifier is 1:5:15:2;

[0107] Step 102. Add ammonia water dropwise to the activated composite fiber prepared in step 101, perform ultrasonic treatment at room temperature and 2000 Hz for 30 min, and then perform constant temperature reaction at 50° C. in a water bath for 18 h to obtain a crude composite fiber;

[0108] Among them, the mass ratio of activated composite fiber to ammonia water is 2:1;

[0109] Step 103. The crude composite fiber prepared in step 102 is transferred to room temperature and allowed to stand for 36 hours, and then washed, filtered and dried in sequence to obtain the composite fiber after surface modification.

[0110] (2) The method for preparing the fiber-modified unsaturated polyester resin comprises the following steps:

[0111] Step 201. Put the composite fiber, unsaturated polyester resin base material, dispersant and ethyl acetate into a high-speed dispersing kettle in sequence, and disperse them at 50° C. and 2000 rpm for 30 minutes to obtain a crude fiber-modified resin;

[0112] The mass ratio of composite fiber, unsaturated polyester resin base material, dispersant and ethyl acetate is 2:7:1:10;

[0113] Step 202. Ethyl acetate and deionized water are added to the crude fiber-modified resin prepared in step 201 in sequence, and dispersed for 15 minutes in a water bath at 45° C., nitrogen atmosphere, and 2600 rpm to obtain an emulsion;

[0114] Among them, the mass ratio of crude fiber modified resin, ethyl acetate and deionized water is 2:3:10;

[0115] Step 203. The emulsion prepared in step 202 is transferred to a spray dryer, and after atomization drying at a dryer inlet temperature of 155°C and a dryer outlet temperature of 95°C, it is allowed to stand and cool at 16°C to obtain a fiber-modified unsaturated polyester.

[0116] (3) The preparation method of the filler comprises the following steps:

[0117] According to the filler component table shown in Table 2, calcium carbonate A, calcium carbonate B, α-alumina, carbon nanotubes and hollow microspheres were put into a stirring tank in sequence, and then a silane coupling agent was added dropwise into the stirring tank. After stirring for 20 minutes at 100 rpm and soaking for 2 hours, the filler was obtained by washing, filtering and drying in sequence.

[0118] (4) A method for preparing highly stain-resistant artificial marble comprises the following steps:

[0119] Step 301. According to the component table shown in Table 3, fiber-modified unsaturated polyester resin, filler, accelerator, dispersant and initiator are sequentially added into a stirring kettle, and dispersed evenly in a water bath at 65° C., 2200 rpm, nitrogen atmosphere, and -0.05 MPa to obtain artificial marble slurry;

[0120] Step 302. After applying a proper amount of release agent on the inner surface of the molding mold, the artificial marble slurry prepared in step 301 is transferred to the mold, solidified under the conditions of 150°C and 0.5Mpa, and cooled and demolded to obtain highly stain-resistant artificial marble.

[0121] (5) An artificial marble surface treatment agent comprises the following steps:

[0122] According to the component list shown in Table 4, deionized water silicate, neutral silica sol, propyltrimethoxysilane, methyl silicate and additives were sequentially put into a stirring tank, dispersed for 15 minutes at room temperature and 1200 rpm, and the pH value was adjusted to 8.0 to obtain an artificial marble surface treatment agent.

[0123] (6) A method for preparing artificial marble for kitchen use comprises the following steps:

[0124] The artificial marble surface treatment agent prepared above was sprayed on the outer surface of the artificial marble prepared above using a spray gun, and after drying at room temperature, kitchen artificial marble was obtained. The average thickness of the coating on the outer surface of the artificial marble was 0.8 mm.

[0125] Comparative Example 1

[0126] As shown in Tables 1-3, in Example 3, the fiber-modified unsaturated polyester resin is replaced with a conventional unsaturated polyester resin, that is, the composite fiber is completely removed during the preparation of the fiber-modified unsaturated polyester resin, and the removed part is supplemented with unsaturated polyester resin, and the remaining components and operating steps remain unchanged.

[0127] Comparative Example 2

[0128] As shown in Tables 1-3, all the composite fibers in the fiber-modified unsaturated polyester resin in Example 3 are replaced with single glass fibers, and the removed parts are supplemented with unsaturated polyester resin, while the remaining components and operation steps remain unchanged.

[0129] Comparative Example 3

[0130] As shown in Table 1-3, in Example 3, the carbon nanotubes in the filler were removed and then artificial marble was prepared. The removed portion was supplemented with calcium carbonate A, and the remaining components and operation steps remained unchanged.

[0131] Comparative Example 4

[0132] As shown in Tables 1-3, in Example 3, the carbon nanotubes in the filler are removed and then artificial marble is prepared, the removed portion is supplemented with calcium carbonate A, and the fiber-modified unsaturated polyester resin is replaced with a conventional unsaturated polyester resin, that is, during the preparation of the fiber-modified unsaturated polyester resin, the composite fiber is completely removed, the removed portion is supplemented with an unsaturated polyester resin, and the remaining components and operating steps remain unchanged.

[0133] Table 3 Composition of artificial marble

[0134] Components (parts) Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Fiber modified unsaturated polyester resin 24.6 servings 29.4 copies 34.5 servings - 34.5 servings 34.5 servings Conventional unsaturated polyester resin - - - 34.5 servings - - 34.5 servings filler 44.5 servings 50.3 copies 53.6 copies 53.6 copies 53.6 copies 53.6 copies 53.6 copies Accelerator 1.2 servings 2.1 serving 4.5 servings 4.5 servings 4.5 servings 4.5 servings 4.5 servings Dispersants 1.1 serving 2.1 serving 2.2 servings 2.2 servings 2.2 servings 2.2 servings 2.2 servings Initiator 5.1 serving 5.5 servings 5.7 servings 5.7 servings 5.7 servings 5.7 servings 5.7 servings

[0135] The samples prepared in Examples 1-3 and Comparative Examples 1-4 were subjected to the following tests:

[0136] Test 1: The porosity of test pieces 1-3 and test pieces 5-8 was measured according to GB T 23561.4-2009;

[0137] Test 2: Extreme condition simulation test A, test pieces 1-10 of the same size (5 cm long, 5 cm wide, 3 cm thick) were immersed in dark soy sauce at the same time to simulate the stain resistance of artificial marble under extreme kitchen use scenarios. After soaking for a certain period of time, the test pieces were transferred from the dark soy sauce pool to the clean water pool for immersion and cleaning, and the appearance of the test pieces was observed to determine their stain resistance;

[0138] Test 3: Extreme condition simulation experiment B, where test pieces 1-10 of the same size (5 cm in length, 5 cm in width, and 3 cm in thickness) were immersed in industrial chili oil at the same time to simulate the stain resistance of artificial marble under extreme kitchen use scenarios. After soaking for a certain period of time, the test pieces were transferred from the chili oil pool to a clean water pool for immersion and cleaning, and the appearance of the test pieces was observed to determine their stain resistance.

[0139] Test 4: Test pieces 4, 9 and 10 were tested according to GB / T 1720-2020 to measure the adhesion strength of the marble surface treatment agent;

[0140] Test pieces 4, 9 and 10 were immersed in a 10% NaCl solution with a mass fraction of 5.0. After a certain period of time, the adhesion strength of the marble surface treatment agent was measured again under dry conditions according to GB / T 1720-2020 standard to evaluate the anti-aging performance of the surface treatment agent.

[0141] The highly stain-resistant artificial marbles prepared in Examples 1-3 are test pieces 1-3, respectively; the kitchen artificial marble coated with a surface treatment agent prepared in Example 3 is test piece 4; the artificial marbles prepared in Comparative Examples 1-4 are test pieces 5-8, respectively; after the marble surface treatment agent prepared in Example 3 is applied on the surface of the artificial marble prepared in Comparative Example 1, test piece 9 is obtained; after the marble surface treatment agent prepared in Example 3 is applied on the surface of the artificial marble prepared in Comparative Example 3, test piece 10 is obtained; after the marble surface treatment agent prepared in Example 3 is applied on the surface of the artificial marble prepared in Comparative Example 4, test piece 10 is obtained; the test results are shown in Table 5 below.

[0142] Table 5 Test results

[0143] Test Item No. Porosity (%) Simulation experiment A (24 hours) Simulation experiment A (72 hours) Simulation experiment A (168 hours) Simulation experiment B (24 hours) Test piece 1 1.88 After cleaning, the surface of the test piece is smooth and free of soy sauce stains After cleaning, the surface of the test piece is smooth and free of soy sauce stains After cleaning, the surface of the test piece is smooth and free of soy sauce stains After cleaning, the surface of the test piece is smooth and free of oil stains Test piece 2 1.94 After cleaning, the surface of the test piece is smooth and free of soy sauce stains After cleaning, the surface of the test piece is smooth and free of soy sauce stains After cleaning, the surface of the test piece is smooth and free of soy sauce stains After cleaning, the surface of the test piece is smooth and free of oil stains Test piece 3 1.79 After cleaning, the surface of the test piece is smooth and free of soy sauce stains After cleaning, the surface of the test piece is smooth and free of soy sauce stains After cleaning, the surface of the test piece is smooth and free of soy sauce stains After cleaning, the surface of the test piece is smooth and free of oil stains Test piece 4 - After cleaning, the surface of the test piece is smooth and free of soy sauce stains After cleaning, the surface of the test piece is smooth and free of soy sauce stains After cleaning, the surface of the test piece is smooth and free of soy sauce stains After cleaning, the surface of the test piece is smooth and free of oil stains Test piece 5 18.72 After cleaning, the glossiness of the test piece decreased and the surface became light brown. After cleaning, the glossiness of the test piece further decreased and the surface became brown. After cleaning, the glossiness of the test piece further decreased and the surface became dark brown. After cleaning, the glossiness of the test piece decreased and the surface was light red. Test piece 6 8.65 After cleaning, the surface of the test piece is smooth and free of soy sauce stains After cleaning, the surface of the test piece is smooth and free of soy sauce stains After cleaning, the glossiness of the test piece further decreased and the surface became light brown. After cleaning, the surface of the test piece is smooth and free of oil stains Test piece 7 6.43 After cleaning, the surface of the test piece is smooth and free of soy sauce stains After cleaning, the surface of the test piece is smooth and free of soy sauce stains After cleaning, the glossiness of the test piece further decreased and the surface became light brown. After cleaning, the surface of the test piece is smooth and free of oil stains Test piece 8 33.81 After cleaning, the glossiness of the test piece decreased significantly and the surface became brown. After cleaning, the glossiness of the test piece further decreased and the surface became dark brown. After cleaning, the glossiness of the test piece is close to 0, and the surface is dark brown. After cleaning, the glossiness of the test piece decreased significantly, and the surface showed a texture enriched with chili oil. Test piece 9 - After cleaning, the surface of the test piece is smooth and free of soy sauce stains After cleaning, the surface of the test piece is smooth, without large areas of soy sauce stains, and there are local textures formed by soy sauce enrichment. After cleaning, the surface of the test piece is smooth, the soy sauce texture spreads to form large soy sauce patches, the glossiness is significantly reduced, and the surface is brown After cleaning, the surface of the test piece is smooth and free of oil stains Test piece 10 - After cleaning, the surface of the test piece is smooth and free of soy sauce stains After cleaning, the surface of the test piece is smooth and free of soy sauce stains After cleaning, the surface of the test piece is smooth, without large areas of soy sauce stains, and there are more textures formed by soy sauce enrichment in some parts After cleaning, the surface of the test piece is smooth and free of oil stains

[0144] Table 5 Test results table

[0145] Test Item No. Simulation experiment B (72 hours) Simulation experiment B (168 hours) Adhesion strength Adhesion strength after aging for 24h Adhesion strength after aging for 72h Test piece 1 After cleaning, the surface of the test piece is smooth and free of oil stains After cleaning, the surface of the test piece is smooth and free of oil stains - - - Test piece 2 After cleaning, the surface of the test piece is smooth and free of oil stains After cleaning, the surface of the test piece is smooth and free of oil stains - - - Test piece 3 After cleaning, the surface of the test piece is smooth and free of oil stains After cleaning, the surface of the test piece is smooth and free of oil stains - - - Test piece 4 After cleaning, the surface of the test piece is smooth and free of oil stains After cleaning, the surface of the test piece is smooth and free of oil stains 1 1 1 Test piece 5 After cleaning, the glossiness of the test piece further decreased and the surface became red. After cleaning, the glossiness of the test piece further decreased and the surface became red. - - - Test piece 6 After cleaning, the surface of the test piece is smooth and free of oil stains After cleaning, the surface of the test piece is enriched with chili oil texture - - - Test piece 7 After cleaning, the surface of the test piece is smooth and free of oil stains After cleaning, the surface of the test piece is smooth and free of oil stains - - - Test piece 8 After cleaning, the glossiness of the test piece is significantly reduced, and the surface shows a large area of ​​oil spots due to the enriched chili oil texture. After cleaning, the glossiness of the test piece decreased significantly, the area of ​​the oil spot increased significantly, and the surface of the test piece was red, with a redness close to that of chili oil. - - - Test piece 9 After cleaning, the surface of the test piece is enriched with chili oil texture After cleaning, the glossiness of the test piece is significantly reduced, and the surface shows a large area of ​​oil spots due to the enriched chili oil texture. 4 6 7 Test piece 10 After cleaning, the surface of the test piece is enriched with chili oil texture After cleaning, the glossiness of the test piece is significantly reduced, and the surface shows a large area of ​​oil spots due to the enriched chili oil texture. 3 6 7

[0146] It can be seen from the above test results that the porosity of the artificial marble test pieces prepared from test pieces 1-3 is significantly reduced. Figure 1-2 As shown, the unsaturated polyester resin is modified by using a surface-treated composite fiber, and SiO2 grains with a particle size of nanometers are branched on the surface of the composite fiber, which significantly increases the specific surface area of ​​the composite fiber. During the blending process with the unsaturated polyester resin, the binding sites are significantly increased. During the chain extension process, the composite fiber can form a C-Si-H bond with the resin, which significantly improves the binding ability. An interpenetrating network can be formed inside the resin. After blending with the filler, due to the composite fiber in the resin and the carbon nanotubes in the filler, when the large particle filler is embedded in the resin, the SiO2 grains on the composite fiber can absorb the carbon nanotubes and the small particle filler to fill the gap. The carbon nanotubes can fit closely with the gap through the C-Si-H bond, refine the internal structure of the artificial marble, and then significantly reduce the porosity of the artificial marble, making the artificial marble structure more compact. It can be seen from the test results in Table 5 that the porosity of the artificial marble provided by the present application is equivalent to that of natural granite, which is significantly higher than that of natural marble.

[0147] In Comparative Example 1, the composite fiber is removed. On the one hand, the fiber structure cannot be introduced into the resin to improve the binding ability of the resin during the blending process. On the other hand, the C-Si-H bond cannot be introduced into the system, the filling effect is significantly reduced, and the porosity of the artificial marble is significantly improved. In Comparative Example 2, the composite fiber is replaced by a single glass fiber. Because the mechanical properties of the single glass fiber are poor, it is impossible to maintain a long chain segment during the blending process. The binding sites in the system are reduced compared with the composite fiber, the filling effect is weak, and the porosity of the artificial marble is improved. In Comparative Example 3, the carbon nanotubes are removed, the C-Si-H bonds in the system are reduced, and the filling effect is correspondingly reduced. However, due to the high strength and surface of the composite fiber, the porosity of the artificial marble can still be maintained at a low level. In Comparative Example 4, the composite fiber and the carbon nanotubes are completely removed, the C-Si-H bond content in the system drops sharply, the filling effect is significantly reduced, and the porosity of the artificial marble is equivalent to that of the marble commonly sold on the market;

[0148] It can be seen from the above test results that by introducing the surface-modified composite fibers, when the marble surface treatment agent is coated on the marble, the silicate in the marble surface treatment agent will form a C-Si-H bond with the composite fibers, and the carbon nanotubes in the filler can provide capillary action, which significantly improves the adhesion between the surface treatment agent and the marble surface, thereby improving the temperature resistance and anti-aging properties of the artificial marble.

[0149] The above are only embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A highly stain-resistant artificial marble, characterized in that: The invention is composed of the following components by weight: 22-35 parts of fiber-modified unsaturated polyester resin, 43-55 parts of filler, 1-5 parts of accelerator, 1-5 parts of dispersant and 3-8 parts of initiator; The fiber-modified unsaturated polyester resin is an unsaturated polyester resin obtained by modifying composite fibers; The composite fiber is a composite of any two or more of carbon fiber, glass fiber, PVA fiber, and PE fiber; The composite fiber is prepared after surface modification treatment, and the surface modification treatment of the composite fiber includes the following steps: Step 101. Put the composite fiber, tetraethyl orthosilicate and ethanol into a reaction kettle in sequence, and add the composite surface modifier drop by drop at room temperature and 200 rpm, and after the addition is completed, the activated composite fiber is obtained; Step 102. Add ammonia water dropwise to the activated composite fiber prepared in step 101, perform ultrasonic treatment at room temperature and 2000 Hz for 30 min, and then perform constant temperature reaction at 50° C. in a water bath for 18 h to obtain a crude composite fiber; Step 103. The crude composite fiber prepared in step 102 is transferred to room temperature and allowed to stand for 36 hours, and then washed, filtered and dried in sequence to obtain the composite fiber with surface modification treatment; In step 101, the composite surface modifier is obtained by mixing CTAB and a silane coupling agent in a mass ratio of 1:1; The preparation method of the fiber-modified unsaturated polyester comprises the following steps: Step 201. Put the composite fiber, unsaturated polyester resin base material, dispersant and ethyl acetate into a high-speed dispersing kettle in sequence, and disperse them at 50° C. and 2000 rpm for 30 minutes to obtain a crude fiber-modified resin; Step 202. Ethyl acetate and deionized water are added to the crude fiber-modified resin prepared in step 201 in sequence, and dispersed for 15 minutes in a water bath at 45° C., nitrogen atmosphere, and 2600 rpm to obtain an emulsion; Step 203. The emulsion prepared in step 202 is transferred to a spray dryer, and after atomization drying at a dryer inlet temperature of 155°C and a dryer outlet temperature of 95°C, it is allowed to stand and cool at 10-16°C to obtain a fiber-modified unsaturated polyester.

2. The highly stain-resistant artificial marble according to claim 1, characterized in that: The composite fiber is composed of the following components by weight: 5-8 parts of carbon fiber, 10-23 parts of glass fiber and 1-5 parts of PE fiber; The diameter of the carbon fiber is 8-12 μm, the length of the carbon fiber is 1.5-5.5 mm, and the tensile strength of the carbon fiber is 1950-2560 MPa; The diameter of the glass fiber is 24-50 μm, the length of the glass fiber is 0.7-1.2 mm, and the tensile strength of the glass fiber is 1140-1330 MPa; The diameter of the PE fiber is 15-21 μm, the length of the carbon fiber is 1.2-4.5 mm, and the tensile strength of the carbon fiber is 1950-2560 MPa.

3. The highly stain-resistant artificial marble according to claim 1, characterized in that: The filler is any one of calcium carbonate, alpha alumina, carbon nanotubes and hollow microspheres or a combination of more than one of them.

4. The highly stain-resistant artificial marble according to claim 3, characterized in that: The filler is composed of the following components by weight: 10-15 parts of calcium carbonate A, 5-8 parts of calcium carbonate B, 5-8 parts of α-alumina, 1-5 parts of carbon nanotubes and 1-3 parts of hollow microspheres; The particle size of the calcium carbonate A is 250-330 μm, the particle size of the calcium carbonate B is 50-120 μm, the particle size of the α-alumina is 87-180 μm, and the length of the carbon nanotube is 10-50 mm.

5. The highly stain-resistant artificial marble according to claim 4, characterized in that: The filler is obtained after surface treatment, and the filler surface treatment method comprises the following steps: calcium carbonate A, calcium carbonate B, α-alumina, carbon nanotubes and hollow microspheres are put into a stirring tank in sequence, and then a silane coupling agent is added dropwise into the stirring tank, and after stirring for 20 minutes at 100 rpm, soaking for 2 hours, washing, filtering and drying in sequence to obtain the filler.

6. A method for preparing highly stain-resistant artificial marble according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step 301. Put the fiber-modified unsaturated polyester resin, filler, accelerator, dispersant and initiator into a stirring kettle in sequence, and disperse them uniformly in a water bath at 65° C., 2200 rpm, nitrogen atmosphere, and -0.05 MPa to obtain an artificial marble slurry; Step 302. After applying a proper amount of release agent on the inner surface of the molding mold, the artificial marble slurry prepared in step 301 is transferred to the mold, solidified under the conditions of 150°C and 0.5Mpa, and cooled and demolded to obtain highly stain-resistant artificial marble.

7. An artificial marble surface treatment agent, characterized in that: It is applied to the outer surface of the highly stain-resistant artificial marble according to any one of claims 1 to 5; The artificial marble surface treatment agent is composed of the following components by weight: 7-13 parts of silicate, 8-10 parts of neutral silica sol, 2-4 parts of propyltrimethoxysilane, 12-16 parts of methyl silicate, 0.2-0.5 parts of auxiliary agent and appropriate amount of deionized water; The preparation method of the artificial marble surface treatment agent comprises the following steps: Deionized water silicate, neutral silica sol, propyltrimethoxysilane, methyl silicate and additives are sequentially put into a stirring kettle, dispersed for 10-15 minutes at room temperature and 1200 rpm, and then the pH value is adjusted to 8.0 to obtain an artificial marble surface treatment agent.

8. The artificial marble surface treatment agent according to claim 7, characterized in that: The silicate is composed of the following components by weight: 3-5 parts of lithium silicate with an average particle size of 4.8 mm, 3-5 parts of lithium silicate with an average particle size of 4 mm, and 1-3 parts of sodium silicate with an average particle size of 3.5 mm; The methyl silicate is composed of the following components by weight: 6-8 parts of potassium methyl silicate and 6-8 parts of sodium methyl silicate.

Citation Information

Patent Citations

  • Unsaturated polyester artificial marble and preparation method thereof

    CN103232186A